Reprodutibilidade da palpação unidigital e bidigital durante a avaliação da contração voluntária máxima do assoalho pélvico de mulheres de diferentes faixas etárias e validade de construto com a manometria - Silva, Jordana Barbosa da (Universidade Federal de São Carlos, 2020)
Introduction. Vaginal palpation and manometry are methods used to evaluate pelvic floor musculature (PFM). Through assessment, the physical therapist elaborate the diagnosis and treatment plan, identify possible muscle changes that may predispose PFM dysfunctions and monitors the results of treatment programs. Aims. The objectives of this study were: (1) To evaluate the intra- and inter-rater reliability of unidigital and bidigital vaginal palpation during PFM function by assessment of maximum voluntary contraction (MVC); (2) To analyze the construct's validity between vaginal palpation and manometry. Methods. This is a reliability study conducted according Consensus-based Standards for the Selection of Health Measurement Instruments (COSMIN). 120 women aged between 18 and 80 years participated and were allocated in three groups according to age (G1: 18–35; G2: 36–59; G3: ≥60 years). Three evaluators were responsible for data collection. Examiner A conducted an interview with the participants eligible for the study, by completing a semi-structured questionnaire to analyze the socio-demographic and clinical characteristics; and the Pelvic Floor Disability Index-20 (PFDI-20) to assess the presence of PFM dysfunctions. Then, Examiner A randomized the order of the physical assessment that were performed by Examiners B and C; and the order of vaginal palpation, performed by both examiners, and in two ways: unidigital and bidigital. From 7 to 10 days after the first assessment, Examiner B repeated the uni and bidigital palpation and performed the assessment of PFM function with Peritron manometer (Cardio Design Pty Ltd, Oakleigh, Victoria, Australia). Statistical analysis was performed using the Statistical Package for the Social Sciences (SPSS) software, version 21.0. The reliability of vaginal palpation was analyzed using Cohen's weighted linear kappa test (κw) (0.00–0.20= none to mild; 0.21-0.40=regular; 0.41-0.60=moderate; 0.61-0.80=substantial; and 0.81-1.00= almost perfect) and the construct validity was analyzed using Spearman's correlation test for nonparametric data (0.00–0, 30=little; 0.30-0.50=poor; 0.50-0.70=moderate; 0.70-0.90=high; 0.90-1.00=very high), with significance level 5%. Results. The intra-rater reliability of uni- and bidigital palpation was κw=0.75 and κw=0.58 in G1; κw=0.59 and κw=0.73 in G2; and κw= 0.79 and κw=0.86 in G3, respectively. The inter-rater reliability of unidigital and bidigital palpation was κw=0.52 and κw=0.48 in G1; κw=0.47 and κw=0.52 in G2; and κw=0.50 and κw=0.64 in G3, respectively. Spearman's correlation coefficients were significant (rs=0.79 and rs=0.80) for unidigital and bidigital vaginal palpation, respectively. Conclusion. Unidigital and bidigital vaginal palpation are indicate to evaluate women between 18 to 59 years old, but bidigital palpation seems more reproducible in women aged 60 or more when two examiners performed the evaluation. During measurements performed by a single examiner, unidigital palpation is more reproducible in women between 18 to 35 years old, while bidigital palpation is more reproducible in women over 35 years old. Both uni- and bidigital palpation have high measures of validity.
Reliability of unidigital and bidigital vaginal palpation during the evaluation of maximal voluntary contraction of female pelvic floor from different age groups and validity construct of manometry
Keywords: Assoalho pélvico; Palpação; Manometria; Saúde da mulher; Reprodutibilidade dos testes; Fisioterapia; Pelvic floor; Palpation; Manometry; Women's health; Reproducibility of tests; Physiotherapy; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL